2003
DOI: 10.1002/ajmg.a.20246
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of Down syndrome: Ten year experience in the Israeli population

Abstract: Second trimester maternal serum biochemical markers, introduced between 1990 and 1995, were supplemented with new ultrasound methods at 14-16 weeks and first trimester biochemical markers between 1995 and 2000. This study evaluated the effectiveness of a Down syndrome (DS) prevention program among the Israeli Jewish population between 1990 and 2000. We collected data on the total number of prenatal tests performed on Israeli Jewish women, DS cases detected prenatally and DS livebirths in Israel during these ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 19 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…Although among Muslims in Israel fewer than 30% of women at risk for Down's syndrome undergo prenatal diagnostic testing, 14 early prenatal testing by CVS for monogenic disorders such as thalassemia is well accepted. 15,16 This may be explained by differences in the perceived severity of the type of disorders and the possibility of early diagnosis at a stage when termination is still permissible according to religion and tradition.…”
Section: Discussionmentioning
confidence: 99%
“…Although among Muslims in Israel fewer than 30% of women at risk for Down's syndrome undergo prenatal diagnostic testing, 14 early prenatal testing by CVS for monogenic disorders such as thalassemia is well accepted. 15,16 This may be explained by differences in the perceived severity of the type of disorders and the possibility of early diagnosis at a stage when termination is still permissible according to religion and tradition.…”
Section: Discussionmentioning
confidence: 99%
“…For technical reasons data for the year 1991 were missing. We analysed 1,108,449 births, of which 831,505 were in the Jewish population and 276,944 in the non-Jewish (mostly Arab) sector (Shohat et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Benn et al [2004] reported a 50% reduction in the number of amniocenteses at their Connecticut laboratory as a result of increased utilization of serum and sonographic screening from 1991 to 2002. In contrast, during roughly the same 10-year period in Israel, the introduction of serum and sonographic screening had little impact on amniocentesis utilization [Shohat et al, 2003]. Universal screening could shift the demand for laboratory services, with perhaps less need for cytogenetic analyses due to the lower false positive rate of universal screening but a greater demand for serum assays and sonography.…”
Section: Discussionmentioning
confidence: 91%